Surgical treatment of hepatocellular carcinoma associated with the metabolic syndrome. Issue 1 (12th November 2012) - Cauchy, F.; Zalinski, S.; Dokmak, S.; Fuks, D.; Farges, O.; Castera, L.; Paradis, V.; Belghiti, J.
Abstract Background: The incidence of metabolic syndrome‐associated hepatocellular carcinoma (MS‐HCC) is increasing. However, the results following liver resection in this context have not been described in detail. Methods: Data for all patients with metabolic syndrome as a unique risk factor for HCC who underwent liver resection between 2000 and 2011 were retrieved retrospectively from an institutional database. Pathological analysis of the underlying parenchyma included fibrosis and non‐alcoholic fatty liver disease activity score. Patients were classified as having normal or abnormal underlying parenchyma. Their characteristics and outcomes were compared. Results: A total of 560 resections for HCC were performed in the study interval. Sixty‐two patients with metabolic syndrome, of median age 70 (range 50–84) years, underwent curative hepatectomy for HCC, including 32 major resections (52 per cent). Normal underlying parenchyma was present in 24 patients (39 per cent). The proportion of resected HCCs labelled as MS‐HCC accounted for more than 15 per cent of the entire HCC population in more recent years. Mortality and major morbidity rates were 11 and 58 per cent respectively. Compared with patients with normal underlying liver, patients with abnormal liver had increased rates of mortality (0 versus 18 per cent; P = 0·026) and major complications (13 versus 42 per cent; P = 0·010). In multivariable analysis, a non‐severely fibrotic yet abnormal underlying parenchyma was a risk factor for major complications (hazard ratio 5·66, 95 per cent confidence interval 1·21 to 26·52; P = 0·028). The 3‐year overall and disease‐free survival rates were 75 and 70 per cent respectively, and were not influenced by the underlying parenchyma. Conclusion: HCC in patients with metabolic syndrome is becoming more common. Liver resection is appropriate but carries a high risk, even in the absence of severe fibrosis. Favourable long‐term outcomes justify refinements in the perioperative management of these patients. Copyright © 2012 British Journal of Surgery Society Ltd. Published by John Wiley & Sons, Ltd.